Analysis of the Strategy for Collecting Zakat, Infaq, and Alms in Increasing the Number of Muzakki at Baznas Kota Sungai Penuh - Putri, Nopela; Sarmigi, Elex (Perisai : Islamic Banking and Finance Journal, 2024)
Zakat is one of the efforts that can be done by the government to help underprivileged people to meet their primary needs by distributing zakat received from Muzakki who have sufficient and even excess assets. This research aims to find out what strategies are applied by the BAZNAS Full River City institution and want to know what factors are an obstacle to raising funds for zakat infaq and sadaqah. The method used in this research is qualitative with a descriptive approach.In this research method using the case study method.The sample of this research was taken from the head of BAZNAS Kota Sungai Penuh. The types of data used in this study are primary data and secondary data with data collection techniques using observation, interviews and documentation. The data obtained in the field was then analyzed by means of data reduction, data presentation and conclusion drawing. The results showed that the fundraising strategy for zakat, infaq and alms at BAZNAS Sungai Penuh focuses on two approaches. First, through direct strategies (offline), such as the establishment of the Zakat Collection Unit (UPZ), promotion by distributing brochures. Second, through indirect strategies (Online), with promotions involving social media, zakat account transfers. And the inhibiting factors of raising funds for zakat, infaq and alms in increasing the number of muzakki in (BAZNAS) Sungai Penuh city are the lack of public understanding of zakat, infaq and alms, the collection of zakat, infaq and alms funds that are still not maximally fully active, the donors (muzakki) who have not reached the nishab and there are still many muzakki who pay zakat directly to mustahik.